Effects of the leucovorin shortage: Pilot study investigating cost, efficacy, and toxicity comparison of low fixed-dose versus body surface area-adjusted leucovorin dosing in patients with resectable colon or metastatic colorectal cancer. (April 2017) - Shank, Brandon R; Seung, Amy H; Kinsman, Katharine; Newman, Matthew J; Donehower, Ross C; Burton, Bradley
Purpose: As a result of the leucovorin shortage, we switched from BSA-adjusted to low fixed-dose leucovorin in patients with colon cancer receiving fluorouracil-containing therapy. Methods: A retrospective, pilot study of adults receiving intravenous leucovorin as part of a fluorouracil-containing treatment was conducted including individuals with stage II or III colon or newly diagnosed metastatic colorectal cancer. One low fixed-dose (leucovorin 50 mg) patient was matched by the investigator to one BSA-adjusted (leucovorin 200–500 mg/m 2 /dose) patient on disease stage and age. The objectives were to compare cost of alternative dosing strategies as well as efficacy and adverse event rates. Only patients being treated in the first-line metastatic colorectal cancer setting were included in the efficacy analysis. Results: Fifty-eight patients were included. Leucovorin cost was reduced by 7- to 14-fold, and we were able to conserve a total of 1580–3400 doses of leucovorin by changing to fixed-dose (estimated from 200 mg/m 2 or 400 mg/m 2 dosing strategies, respectively). No statistically significant differences in progression-free survival ( p  = 0.254), overall survival ( p  = 0.923), or complications resulted. Conclusion: Our decision to reduce the dose of leucovorin allowed us to conserve supply and control cost. The small sample size did not allow us to detect differences in efficacy or adverse event rates, and thus a larger study would be required to confirm our findings that efficacy was not compromised nor adverse effects greater.